Research of mechanism of receipt of gas environment with outwardly in intercontact space of surfaces of friction. Рart 2. - Криштопа, Л.І. (Problems of Tribology, 2015)
Kryshtopa L.I. Research of mechanism of receipt of gas environment with outwardly in intercontact space of surfaces of friction. Рart 2.The article is devote to the problem of laboratory researches of mechanism of receipt of gas environment with out-wardly to intercontact space of friction surfaces and create the physical and chemical model of mechanism of migration of environment to the friction contact. For the design of model of migration of environment mechanism which considered to the friction contact adsorption, pumping and crack effects take place. A gas dynamic at intercontact space has a difficult character depending on the modes of friction and mechanical, physical and chemical properties of friction surface can get the positive or negative value. Surplus pressure hinders to migra-tion in between contact space of environment and creates terms for formation areas of pellicle starvation. Subsequent re-searches will be devoted to research of gas dynamic at intercontact space for destructions of phenol formaldehyde materials.